Microalbuminuria Prevelance and Associated Factors in Obese Patients Applying to Primary Care in Malatya City Center (Annals of Medical Research, 2021)
Aim: The purpose of this study is to determine frequency of microalbuminuria and to analyze related factors in obese patients in primary health care.
Keywords: Obesity; Primary Health Care; Microalbuminuria.